Water boatmen (Heteroptera: Nepomorpha: Corixidae) of Romania - Berchi, Gavril Marius; Rădac, Ioan Alexandru; Boda, Pál; Kment, Petr (Zootaxa, 2024)
We here update the distribution and provide a checklist of the water boatmen (Hemiptera: Heteroptera: Corixoidea: Corixidae) of Romania based on country-wide sampling, a literature survey, and private and museum collections. The Romanian fauna currently comprises 25 water boatmen species and subspecies in eight genera and two subfamilies. The occurrence of Glaenocorisa propinqua (Fieber, 1860), Arctocorisa carinata carinata (Sahlberg, 1819), and Corixa panzeri Fieber, 1848, all known from old and single records, is here confirmed. The first record of an intermediate shape of the pala between Sigara falleni (Fieber, 1848) (triangular) and S. iactans Jansson, 1983 (trapezoidal) is reported from the southeastern European population of the latter, suggesting possible hybridization.